TEROBOSAN HUKUM MAHKAMAH KONSTITUSI (Analisis Tentang Putusan MK Nomor: 41/PHPU.D-VI/2008) - Muhammad Fauzan (Faculty of Law, Universitas Jenderal Soedirman, 2009)
Decision of Constitutional Court of Republic Of Indonesia Number 41/PHPU.D-VI/2008 is law breakthrough / invention of law ( rechtsvinding) because judge is not funnel of law, Judge have freedom in verdicting is reflection of independence / freedom of judge based on justice values and living law which growth and expand in society. By tekstual decision of Constitutional Court Number 41/PHPU.D-VI/2008 earning isn't transgression because reason of consideration of judge command the Lokal Commission of General Election of East Java to execute re- balloting can be concluded do not fulfill clauses as based in Section 219 sentence ( 1) and ( 2) of The 2008 General Election Code Number 10, and have potency to impinge rule of Section 233 sentence (3) of The 2008 Local Government Code Number 12 Second Change of The 2004 of the Local Government Code Number 32. Kata Kunci : Terobosan Hukum